Implementasi Model Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Aktivitas dan Hasil Belajar Passing Bola Voli - Purwanto, Didik (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2023)
This study aims to increase the activity and learning outcomes of the basic techniques of passing (up and down) volleyball through the implementation of the STAD type cooperative learning model in class VIII A students of SMP Negeri 3 Balinggi. This type of research is classified as classroom action research in the form of a teacher as a researcher, which is carried out in 2 cycles and 2 meetings in each cycle. The research subjects were class VIII A students at SMP Negeri 3 Balinggi for the academic year 2022/2023 consisting of 31 students, namely 17 boys and 14 girls. The collected data were analyzed using descriptive statistical analysis. The results showed that in the first cycle the average learning outcomes of students with classical completeness were 79.41% in the good category. While in cycle II, the average learning outcomes of students with classical mastery of 100% is very good category. Based on the results of data analysis and discussion, it was concluded that the activity and learning outcomes of basic volleyball passing techniques (bottom and top) increased through the implementation of the STAD type cooperative learning model.